First record of the family Schizodactylidae (Orthoptera: Ensifera) from Thailand, with the description of a new species - Dawwrueng, Pattarawich; Panitvong, Nonn; Mooltham, Kanin; Meebenjamart, Pongpipat; Jaitrong, Weeyawat (Zootaxa, 2018)
A new species of dune cricket in the family Schizodactylidae, Schizodactylus salweenensis sp. nov. is described from Salween River, Mae Hong Son Province, northwestern Thailand based on both males and females. The Schizodactylidae is recorded for the first time in Thailand. The new species is most similar to Schizodactylus tuberculatus Ander, 1938 and Schizodactylus burmanus Uvarov, 1935 in the morphology of male subgenital plate, but mainly differs in the shape of subgenital plate apex, and the spurs of hind tibiae. The type series was collected from sand dunes along the river. This cricket reaches adulthood during the rainy season.